2020
DOI: 10.1161/strokeaha.120.028934
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Acting Oral Anticoagulants Versus Warfarin in Medicare Patients With Chronic Kidney Disease and Atrial Fibrillation

Abstract: Background and Purpose: The comparative effectiveness of direct-acting oral anticoagulants, compared with warfarin, for risks of stroke/systemic embolism, major bleeding, or death have not been studied in Medicare beneficiaries with atrial fibrillation and nondialysis-dependent chronic kidney disease. Methods: Medicare data from 2011 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 44 publications
2
29
1
1
Order By: Relevance
“…Medicare data showed that apixaban, compared with warfarin, was associated with a decreased risk of stroke or systemic embolism and major bleeding. Risks for both outcomes with rivaroxaban and dabigatran did not differ from risks with warfarin in patients with impaired renal function [36]. In the present study, GFR < 60 mL/min/1.73 m 2 was a factor predisposing the choice of apixaban and diminishing the chance of using rivaroxaban or dabigatran.…”
Section: Discussioncontrasting
confidence: 40%
“…Medicare data showed that apixaban, compared with warfarin, was associated with a decreased risk of stroke or systemic embolism and major bleeding. Risks for both outcomes with rivaroxaban and dabigatran did not differ from risks with warfarin in patients with impaired renal function [36]. In the present study, GFR < 60 mL/min/1.73 m 2 was a factor predisposing the choice of apixaban and diminishing the chance of using rivaroxaban or dabigatran.…”
Section: Discussioncontrasting
confidence: 40%
“…Appropriate anticoagulant therapy and frequent renal function monitoring are crucial in these patients [37]. Moreover, taking into account concomitant increased risk of bleeding in patients with CKD and reported kidney injury in patients on warfarin during excessive anticoagulation non-vitamin K oral anticoagulants (unless contraindicated), especially apixaban, could be preferred over vitamin K antagonists [38][39][40][41][42]. Left atrial appendage occlusion might be an option in patients with severe CKD who have contraindications to lifelong anticoagulant therapy [43].…”
Section: Discussionmentioning
confidence: 99%
“…14 Other primary literature investigating DOAC use in ESRD has used warfarin as a comparator, which represents a limitation for these data. [15][16][17][18][19] As such, clinicians should be cautious when contemplating the use of anticoagulation for primary prevention of stroke in this population.…”
Section: Severe Renal Impairmentmentioning
confidence: 99%
“…[20][21][22][23] Among the DOAC class, apixaban seems to be the safest and best tolerated agent in ESRD, which is intuitive given its low renal clearance. 15,16 Retrospective analyses comparing apixaban to warfarin in CKD stage IV, V, or dialysis suggest that it is at least as efficacious as warfarin in preventing thromboembolic events with significantly less major bleeding in some analyses. 16 Mixed data have been reported addressing rivaroxaban safety compared to warfarin in ESRD, with prospective data indicating a reduced risk of major bleeding, and retrospective data indicating an increased risk of death or hospitalization from bleeding.…”
Section: Severe Renal Impairmentmentioning
confidence: 99%